Long‐term biodiversity trajectories for pest‐managed ecological restorations: eradication vs. suppression. Issue 2 (18th January 2021) - Binny, Rachelle N.; Innes, John; Fitzgerald, Neil; Pech, Roger; James, Alex; Price, Robbie; Gillies, Craig; Byrom, Andrea E.
Abstract: Invasions by alien pest species contribute heavily to global biodiversity decline, with invasive mammals having some of the greatest impacts on endemic biota. Pest management within ecological restorations is therefore critical for conserving threatened biota. Coordinating restoration efforts at global scale requires evidence of the relative efficacy of different pest‐managed restoration approaches ("regimes") for enhancing biodiversity. Our national meta‐analysis of 447 biodiversity responses across 16 ecological restorations quantifies significant benefits for biodiversity over two decades and multiple trophic levels, and across a spectrum of invasive mammal suppression‐to‐eradication regimes. Deeply endemic species had the strongest responses to pest control compared with recent native or introduced biota. Using this information, we predict levels of pest suppression required to confer biodiversity benefits, to guide future management strategies. Our findings provide new evidence that invasive pest control is an effective approach to ecological restoration, to aid decision‐makers in setting objectives and making targeted investments.